Craft activities in groups at meeting places: supporting mental health users' everyday occupations. (March 2014) - Horghagen, Sissel; Fostvedt, Berit; Alsaker, Sissel
Abstract Aim: People with mental health illness often lose everyday occupations that give life consistency. Recovery is therefore supposed to take place through transactions between person and environment. Such transactions might occur at meeting places. These services offer voluntary participation to support participants' inclusion in the society, and are part of the Norwegian Mental Health reforms. Crafts are one of the activities used at the meeting places. There is limited empirical research on the interventions of activities at these services. Therefore the aim of this study was to explore how the participants' engagements in craft activities in a group supported their way of managing everyday occupations. Methods: Ethnography was chosen as a design, to meet the study's exploratory aim. The participants in the study were 12 people with long-lasting mental health illness. Results: Procedures for paradigmatic analysis were followed, and brought forward three themes: doing crafts in a group facilitated stability and routines, skills and abilities, and peer support. The discussion reflected knowledge and experiences of crafts as an activity with a low-risk threshold for participation and its healing value. How the doing of craft activities in a group offered transactional space to gain experiences to manage everyday occupations was further discussed.